Inhibitory effect of xanthan gum and synergistic surfactant additives for mild steel corrosion in 1 M HCl. (20th January 2016) - Mobin, Mohammad; Rizvi, Marziya
Highlights: Xanthan gum was investigated as novel corrosion inhibitor for mild steel in 1 M HCl. Effect of surfactants on inhibition behavior of xanthan gum was also investigated. Methods include gravimetric, electrochemical, SEM and quantum chemical analysis. Xanthan gum acts as a mixed-type inhibitor. Surfactants synergistically increased the inhibition efficiency of xanthan gum. Abstract: Natural polymer xanthan gum (XG) was investigated as eco friendly corrosion inhibitor for mild steel in 1 M HCl at 30 °C, 40 °C, 50 °C and 60 °C, respectively. The inhibition studies were performed using gravimetric analysis, potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), quantum chemical calculations, scanning electron microscopy (SEM), and UV–visible spectrophotometry. XG significantly reduces the corrosion rates of mild steel. The inhibition efficiency (IE) of the XG increased with increase in concentration, but decreased with temperature; the maximum IE of 74.24% was obtained at concentration of 1000 ppm at 30 °C. The inhibiting action of XG is synergistically enhanced on addition of very small amount of surfactants sodium dodecyl sulfate (SDS), cetyl pyridinium chloride (CPC) and Triton X-100 (TX). The effect of SDS is more pronounced than other surfactants. Potentiodynamic polarization studies confirm XG as a mixed type inhibitor. Results of weight loss measurements are in good agreement of the results of electrochemical measurements. The UV–visible spectroscopic results indicate the formation of complex between XG and Fe 2+ ions during corrosion reaction. Mechanism of inhibition was also investigated by calculating the thermodynamic and activation parameters like Δ G 0, E a, Δ H and Δ S . The adsorption of inhibitor on mild steel surface obeys Langmuir adsorption isotherm. SEM micrographs show a clearly different morphology in presence of XG and XG-surfactant additives and confirmed the existence of an adsorbed protective film on the mild steel surface.